General vocabulary in Thai EFL university students’ writing: A corpus-based lexical study - ANCHALEE VEERACHAISANTIKUL; SUKANYA CHOOTARUT (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: This study, part of a larger task investigation, questions the use of general vocabulary in Thai EFL university students writing. The most common words in English are represented by general vocabulary, which is helpful for language students. The two main goals of the corpus-based lexical study were (a) to compile a list of frequently used general words in Thai EFL university students’ writing and (b) to compare the word list to the New General Service List (NGSL).Method: The authors gathered and analyzed 1,233 writing assignments totaling 661,596 words, all completed by Thai EFL college students. We used WordSmith Tool Version 6 (Scott, 2012) for this research, a concordancing program.Findings: According to our findings, out of the 2,818 NGSL high-frequency words, 1,648 were used frequently throughout the corpus, with this coverage accounting for 1.41 percent of the token total. By comparing our words to the NGSL, we found that most of the core vocabulary in the TEFL Corpus was, in fact, very close to the NGSL.Implications/New Contribution: The study’s findings will inform educators about the role of vocabulary in writing and will be useful to students and curriculum developers as they create resources for the instruction of writing in English as a Foreign Language (EFL) sector. Furthermore, these findings could be used by educators to enhance grammar and vocabulary instruction in the classroom. In addition, students can use these findings to better comprehend and appreciate how English is actually used in the real world to develop their writing skills.